Epidemiology of cutaneous lupus erythematosus and the associated risk of systemic lupus erythematosus: a nationwide cohort study in Denmark. (August 2018) - Petersen, M Prütz; Möller, S; Bygum, A; Voss, A; Bliddal, M
Objectives: The objectives of this paper are to describe the epidemiology of cutaneous lupus erythematosus (CLE) and its subtypes in Denmark, and to investigate the probability of receiving a subsequent diagnosis of systemic lupus erythematosus (SLE) and the related time course. Methods: A nationwide registry-based cohort study was conducted in Denmark based on data from the Danish National Patient Registry from 1998 to 2013 using International Classification of Diseases, Revision 10. Results: We identified 2380 patients with CLE. The annual incidence rate (IR) of CLE was 2.74/100, 000 with a female:male ratio of 4:1. During 12, 047 person-years of follow-up, 8% were diagnosed with SLE. The probability of receiving a subsequent diagnosis of SLE was 12.9% after 10 years taking death as a competing risk into consideration, and the probability was highest among women and patients diagnosed with subacute CLE. The median time until a diagnosis of SLE was 2.05 years. Conclusions: This is the first nationwide study on CLE in Denmark. Although we found the annual IR of CLE and the risk of receiving an additional diagnosis of SLE to be lower than previously described, continued monitoring and thorough information for patients with CLE is important due to the inherent risk of SLE.